Canine distemper virus in wildlife in south‐western Europe. Issue 4 (29th September 2021) - Oleaga, Álvaro; Vázquez, Cristina Blanco; Royo, Luis José; Barral, Thiago Doria; Bonnaire, Debby; Armenteros, José Ángel; Rabanal, Benjamín; Gortázar, Christian; Balseiro, Ana
Abstract: Multi‐host pathogens emerging and re‐emerging at the wildlife–domestic animal interface affect wildlife management and conservation. This is the case of canine distemper virus (CDV), a paramyxovirus closely related to human measles virus and rinderpest virus of cattle. With an area of 10, 603 km 2, Asturias region in Atlantic Spain is a hotspot of carnivore diversity, which includes the largest Eurasian brown bear ( Ursus arctos arctos ) population and one of the largest wolf ( Canis lupus ) populations in south‐western Europe. In 2020–2021, we recorded mortality due to distemper in four carnivore species including three mustelids (Eurasian badger Meles meles, European marten Martes martes and European polecat Mustela putorius ) and one canid (red fox, Vulpes vulpes ). Clinical signs and pathology were similar across species and consistent with the emergence of a highly pathogenic viral strain, with CDV antigen mainly located in the central nervous system, lungs, spleen and lymph nodes. A molecular study in eight wild carnivore species, also including the Iberian wolf, Eurasian brown bear, American mink ( Neovison vison ) and stone marten ( Martes foina ), revealed 19.51% (16/82) of positivity. Phylogenetic analysis demonstrated that CDV belonged to the previously described European lineage. A retrospective serosurvey (2008–2020) showed a high seroprevalence of CDV antibodies (43.4%) in 684 analyzed badgers, indicating a long‐term though not stable viral circulation in this multi‐host community. The possible triggers of the 2020–2021 outbreak and the implications for carnivore management and conservation are discussed.